1980
DOI: 10.1136/adc.55.8.595
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory patterns and risk of sudden unexpected death in infancy.

Abstract: SUMMARY The overnight respiratory patterns of 25 infants at high risk and 42 infants at low risk of sudden unexpected death were studied during the first 6 months of life. 'Risk' was determined using the birth scoring criteria of Carpenter and Emery. Recordings were made at home using a twinchannel radar chest movement detector which was designed to avoid the need for contact with the infant. The recordings were analysed for respiratory frequency, total duration of apnoea, periodic breathing, duration of regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…Higher heart rates in subsequent SIDS infants when compared to controls have been found (37); the authors conclude that although monitoring lacks specificity, it was probably effective in preventing mortality in at risk groups. This phenomenon has been noted by other authors (38).…”
Section: Discussionsupporting
confidence: 88%
“…Higher heart rates in subsequent SIDS infants when compared to controls have been found (37); the authors conclude that although monitoring lacks specificity, it was probably effective in preventing mortality in at risk groups. This phenomenon has been noted by other authors (38).…”
Section: Discussionsupporting
confidence: 88%
“…ignificant new information has been forthcoming in recent decades on sudden infant death syndrome (SIDS) and apnea during early infancy. [1][2][3][4][5][6][7][8] This statement focuses on the epidemiologic aspects of SIDS, the lack of a proven association between episodic apnea and SIDS, strategies for prevention of SIDS, and appropriate use of home cardiorespiratory monitoring.…”
mentioning
confidence: 99%
“…The apnea theory never has been proven despite extensive independent research in the several decades after that report. [1][2][3][4][5] Nevertheless, the home cardiorespiratory monitoring industry, fueled by increasing demand from parents concerned about the risk of SIDS, rapidly developed products aimed at preventing SIDS. 11 Despite the absence of a scientific foundation or evidence of efficacy, 12,13 home cardiorespiratory monitoring continues to be a common practice in this country.…”
mentioning
confidence: 99%
“…Many investigators have reported the proportion of time which newborn infants spend in periodic breathing (5)(6)(7)(8). There has, however, been very little investigation of other features of periodic breathing, and no studies which have investigated the duration of the individual cycle, i.e.…”
mentioning
confidence: 99%